Organic Ingredients Test to SB 03 Clones Growth SB 19 and SB 33 of Sugarcane Plant (Saccharum officinarum L.) - Wiharyanti Nur Lailiya; Setyo Budi; Suhaili Suhaili (Kontribusia : Research Dissemination for Community Development, 2022)
Community service activities are the implementation of the practice of science, technology and cultural arts directly in the community as a dissemination of the Tri Dharma of Higher Education and noble responsibilities in an effort to develop community capabilities, so as to accelerate the growth rate of achieving national development goals. The problem that exists in the foundation is that there is no independent effort and only expects donations from donors so that this service aims to provide input and help the Fadhilah Gresik Princess Orphans Foundation in seeking other funding income in managing the Foundation's operations. The implementation will use the method of giving lectures and direct training to administrators and orphans in learning to make handicrafts, and the training participants are administrators and female orphans with a total of 40 participants. The results of community service have been able to provide entrepreneurial motivation independently which is received with a good response, , and have been able to develop the potential of the Fadhilah Gresik Yatim Putri Foundation through handicrafts from Kur and Knitting ropes with real product results, and can provide solutions to income problems. Operational funds, by selling the handicrafts produced, through direct sales through online social media sales, so that later the Fadhilah Gresik Princess Orphans Foundation, can get income other than donors.